Case Report: Multiple Tick-Borne Diseases and Gastrointestinal Protozoal Infection in a Young Poodle Dog - Putra, I Putu Cahyadi; Meida, Yeocelin Meida; Widyasanti, Ni Wayan Helpina (Universitas Airlangga, 2025)
Co-infections involving tick-borne diseases (TBD) alongside gastrointestinal protozoans are poorly understood in domestic dogs. This case report examines the occurrence of Babesia sp., Ehrlichia sp., and Anaplasma sp. co-infections with Giardia sp. and Amoeba sp. in a three-month-old female poodle. The owner complained that her dog had yellow vomiting and bloody diarrhea, and refused to eat. A physical examination was performed, revealing lethargy, 4% dehydration, bloody diarrhea, mandibular lymphoglandular swelling, and a Rhipicephalus sanguineus tick infestation in the case dog. The parvovirus antigen rapid test kit yielded negative results, whereas the TBD antibody test kit yielded positive results for Anaplasma sp., Babesia sp., and Ehrlichia sp. Infection with Giardia sp. and Amoeba sp. was detected by native stool examination. The dog had lymphocytosis, monocytosis, granulopenia, hyperchromic normocytic anemia, and thrombocytopenia. The therapy provided was metronidazole and doxycycline combination antibiotics, lactated ringer fluid (RL) therapy, vitamin B complex, Sangobion®, Fufang E'jiao Jiang® (FEJ), ondansetron, vitamin K1, kaolin-pectin, and Hill's Prescription Diet® A/D feed. The therapy showed significant improvement during the 3-day hospitalization, and the dog was declared clinically cured after two weeks of treatment.